2017
DOI: 10.3892/mmr.2017.6779
|View full text |Cite
|
Sign up to set email alerts
|

BMP-7 suppresses excessive scar formation by activating the BMP-7/Smad1/5/8 signaling pathway

Abstract: Scarring is the inevitable consequence of wound repair, which may cause significant physical and mental pain to patients when excessive. Bone morphogenetic protein-7 (BMP-7) has been proved to inhibit TGF-β-induced fibrosis in various tissues including dermal papilla cells. However, the effect of BMP-7 on hypertrophic scarring, a common proliferative disorder of dermal fibroblasts, has not been determined. To overcome this problem, the present study established a mouse model of thermal injury to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 28 publications
(27 reference statements)
1
26
0
Order By: Relevance
“…BMP7 is a member of TGFβsuperfamily and has been veri ed to reduce brosis in various tissues [16][17][18][19][20][21][22][23][24][25][47][48][49]. Previous clinical observations indicated that BMP-7 can suppress brosis in renal and myocardial through reducing epithelial-mesenchymal transition and counteracting TGF-β1 signaling pathway [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BMP7 is a member of TGFβsuperfamily and has been veri ed to reduce brosis in various tissues [16][17][18][19][20][21][22][23][24][25][47][48][49]. Previous clinical observations indicated that BMP-7 can suppress brosis in renal and myocardial through reducing epithelial-mesenchymal transition and counteracting TGF-β1 signaling pathway [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Fractional CO2 laser(FCO2L) and 595-nm pulsed dye laser (PDL) are selective phototherapeutics, and have been validated to be effective in therapy of HS [9][10][11][12][13][14], yet their underlying mechanisms remain unclear, and need validation through measurement of bone morphogenetic protein-7(BMP-7) and Fas gene, the two important proteins that affect the prognosis of this condition on molecular study basis. BMP-7, a TGF-β superfamily, has been shown to effectively inhibit the brosis process through regulating cell proliferation, differentiation and apoptosis in various organs and tissuesin series of studies [15][16][17][18][19][20][21][22][23][24][25]. Jin Y [22] found that BMP-7 can undermine TGF-β1 signaling pathway and reduce myocardial brosis to protect the heart, and more reports described that BMP-7 was involved in the development of hypertrophic scars after wound healing and capable of inhibiting the transformation of rat hair mastoid cells (DPCs) into broblasts [16,17,20,21,24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is also very important in the occurrence and development of acute and chronic lung injury (21). It has been found that TGF-β1, interleukin 8 (IL-8) and staphylococcal protein A (SPA) are highly expressed in pulmonary lavage fluid of BDP children (22). TGF-β1 can not only promote the process of pulmonary fibrosis, but also induce the high expression of connective tissue growth factor (CTGF) in lung, thereby promoting the development of pulmonary fibrosis (23).…”
Section: Discussionmentioning
confidence: 99%
“…In a Schistosoma japonicum -infected liver fibrosis model, BMP7 regulated liver fibrosis through the TGF-β-Smad signaling pathway[10]. During the development of liver fibrosis, BMP7 activated Smad1/5/8 to inhibit fibrosis[11,12]. In addition, BMP7 inhibited ColIa1 expression by increasing MMP13 and decreasing TIMP2 expression to further inhibit fibrosis[13].…”
Section: Introductionmentioning
confidence: 99%